An Australian community jury to consider case‐finding for dementia: Differences between informed community preferences and general practice guidelines. (3rd February 2019) - Thomas, Rae; Sims, Rebecca; Beller, Elaine; Scott, Anna Mae; Doust, Jenny; Le Couteur, David; Pond, Dimity; Loy, Clement; Forlini, Cynthia; Glasziou, Paul
Abstract: Background: Case‐finding for dementia is practised by general practitioners (GPs) in Australia but without an awareness of community preferences. We explored the values and preferences of informed community members around case‐finding for dementia in Australian general practice. Design, setting and participants: A before and after, mixed‐methods study in Gold Coast, Australia, with ten community members aged 50‐70. Intervention: A 2‐day citizen/community jury. Participants were informed by experts about dementia, the potential harms and benefits of case‐finding, and ethical considerations. Primary and secondary outcomes: We asked participants, "Should the health system encourage GPs to practice 'case‐finding' of dementia in people older than 50?" Case‐finding was defined as a GP initiating testing for dementia when the patient is unaware of symptoms. We also assessed changes in participant comprehension/knowledge, attitudes towards dementia and participants' own intentions to undergo case‐finding for dementia if it were suggested. Results: Participants voted unanimously against case‐finding for dementia, citing a lack of effective treatments, potential for harm to patients and potential financial incentives. However, they recognized that case‐finding was currently practised by Australian GPs and recommended specific changes to the guidelines. Participants increased their comprehension/knowledge of dementia, their attitude towards case‐finding became less positive, and their intentions to be tested themselves decreased. Conclusion: Once informed, community jury participants did not agree case‐finding for dementia should be conducted by GPs. Yet their personal intentions to accept case‐finding varied. If case‐finding for dementia is recommended in the guidelines, then shared decision making is essential.